2013
DOI: 10.2217/whe.13.35
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Ectopic Pregnancy

Abstract: Ectopic pregnancy remains to be an important cause of maternal morbidity and mortality worldwide, although the incidence has remained unchanged especially in developed countries over the last decade. Several factors are responsible for this, including misdiagnosis and failure to institute timely appropriate treatment aimed at preserving fertility and minimizing the associated morbidity. Recent advances in imaging and biomonitoring have reduced the number of women presenting with ruptured ectopic pregnancy. Any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
34
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 91 publications
5
34
0
2
Order By: Relevance
“…30 A ruptured ectopic pregnancy may manifest itself with abdominal pain, rebound tenderness, and hemorrhagic/hypovolemic shock. 31 In our study we found 56.14% of cases of ruptured ectopic pregnancy were admitted with shock and 85.17% of cases were found to be with hemoperitoneum of more than 500ml of blood.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…30 A ruptured ectopic pregnancy may manifest itself with abdominal pain, rebound tenderness, and hemorrhagic/hypovolemic shock. 31 In our study we found 56.14% of cases of ruptured ectopic pregnancy were admitted with shock and 85.17% of cases were found to be with hemoperitoneum of more than 500ml of blood.…”
mentioning
confidence: 52%
“…4 As far as diagnosis of ruptured ectopics is concerned no particular investigation including serum or urinary beta human chorionic gonadotropin and transvaginal ultrasonography are conclusive and sometimes a surgical approach is required for the differential diagnosis. 5,6 In addition to high risk for mortality, rupture of an ectopic pregnancy could affect future fertility of a woman.…”
mentioning
confidence: 99%
“…Интерстициальная беременность (interstitial ectopic pregnancy) (IEP) Частота патологии в структуре ВБ от 2 до 11% [2,3,4,5,12,[23][24][25]. Глубина публикаций -с 1928 года, отмечен рост числа публикаций с 1998 года (18 за год).…”
Section: таблица 2 /unclassified
“…При относительно небольшой частоте встречаемости (от 5,0% до 8,3% в структу-ре ВБ) эта патология отличается высоким риском массивных кровотечений, вплоть до летального исхода [2][3][4][5]. Рост числа случаев внетубарных ВБ в последние десятилетия связан как с изменением структуры факторов риска, так и с совершенство-ванием методов ранней диагностики, что требует пересмотра диагностических и лечебных протоко-лов [6].…”
unclassified
“…The incidence of ectopic pregnancy is approximately 1–2% of all pregnancies, and ectopic pregnancy accounts for 3–4% of pregnancy‐related deaths . Various noninvasive methods (transvaginal sonography; measurement of β‐human chorionic gonadotropin [β‐hCG] and serum progesterone levels) are used to diagnose ectopic pregnancy …”
Section: Introductionmentioning
confidence: 99%